Accurate location method of branch line break fault in distribution network considering system operation mode - XU Fei; DENG Yanzhen; LIU Honghui; WANG Hui; ZHAO Haiyang (Dianxin kexue)
In the process of locating faults caused by branch line breaks in distribution networks, it is difficult to determine the range of wire breakage due to differences in fault interference branch node identification methods. The relative error of fault location results under different sampling rates is relatively large. Therefore, a accurate location method for branch line break faults in distribution networks considering system operation mode was proposed. The traveling wave transmission path within the power supply system was analyzed based on the topology of the distribution network. A connection matrix for branch nodes was constructed in the distribution network based on the operating mode of the power supply system. Identify the branch nodes affected by wire breakage faults and determine the scope of wire breakage occurrence. Determine the fault occurrence interval based on the characteristic parameters of wire breakage faults. By combining the time difference between zero mode traveling wave and line mode traveling wave, fault location can be obtained, achieving precise positioning of branch line breakage faults in distribution networks. The example analysis results show that after obtaining a high-precision traveling wave signal waveform, the relative error of fault localization results at different sampling rates is reduced by 48% and 12%.